TECHNOLOGY AND PICTURES FOR NURTURING AUTONOMY AND ENHANCING PROFICIENCY: A STUDY OF PREPOSITIONS OF PLACE - Andrias Yulianto; Lailatus Sa'adah; Novi Indrayani (JIU Journal, 2021)
Technology and education have long been collaboratively combined in a range of ways to provide complementary sources of language learning on a variety of topics. Technology exists and has been day by day upgraded to harmonizing with the demands of society especially education system. In fact, the presence of technology has had a tremendous impact on aspects of our lives. Considering the existence of technology in education, this research is designed to investigate how effective picture use and online technology as a learning medium in boosting students’ mastery of preposition of place and how the role of technology in promoting the learners’ autonomy? In line with that, this research is organized with the intention of examining the role of technology in addition to increasing student autonomy, also helping students improve their ability to learn English prepositions. This is survey research which focuses on the collection of information about the role of technology and pictures for nurturing autonomy and English preposition of place proficiency. It uses one group design. Questionnaire was selected for collecting the data as it provided a survey instrument containing the questions in a self-administered survey. Along with questionnaire, this research also used observation instrument. For the purpose of this study the researcher selects 7 (seven) Myanmar ITP (International Training Program) participating in an English short course at EFL University, in India. Based on the observations and analysis of the data obtained from the questionnaire, some conclusions can be drawn, such as participants realized that the use of technology and picture in the classroom facilitate them to study and they found the benefits of using it when they learn English preposition during the intervention. Next, all participants have experienced a positive increase in both the quantity and quality of their writing. along with that, the use of technology and picture is useful in addition to increasing participants' independence and autonomy.